Microstructure and texture evolution of MgZnCe magnesium alloys sheets and associated restoration mechanisms during annealing - Sanjari, M.; Farzadfar, S.F.; Sakai, T.; Utsunomiya, H.; Essadiqi, E.; Jung, In-Ho; Yue, S. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2013)
The texture evolution in four MgZnCe alloys was compared to that of Mg3Al1Zn (AZ31) alloy following rolling and subsequent isothermal annealing. All the as-cast and homogenized alloys were rolled through two stages that can be characterized as rough rolling and finish rolling, respectively. To investigate the effect of finish rolling temperature, one finish rolling pass with 65% reduction in thickness was performed at 300°C and 450°C. Of the studied compositions, the Mg1Zn1Ce, which had the highest Ce/Zn ratio, showed the weakest as-rolled texture and homogenous shear banding/twinning. Changing the Zn content changed particle size and, in alloys subject to texture weakening, the static recrystallization mechanism altered. On annealing, the maximum intensity of basal pole figures decreases as recrystallization progresses. The Mg1Zn1Ce (with the highest Ce/Zn), texture weakening is maintained even after full recrystallization, when grain coarsening occurs. However, in the Mg4Zn1Ce and AZ31 alloys, texture strengthening occurs when grain coarsening occurs, and the double split basal peak is replaced by a single peak. In these two alloys, grain coarsening is also accompanied by a bimodal grain size whereas in the Mg1Zn1Ce alloy, the grain coarsening leads to a uniform grain size. It is concluded that the differences between the Ce bearing alloys are related to Zn; increasing Zn decreases the solubility of Ce, which can influence the texture changes.